The end-times in medieval German literature : sin, evil, and the Apocalypse - Hintz, Ernst Ralf; Pincikowski, Scott E., 1968- (Studies in German literature, linguistics, and culture., 2019)
"The contemporary fascination with the end of the world and of life as we know it would not have surprised our counterparts a millennium ago; only the fact that such an end has not yet occurred. Current visions of the apocalypse encompass climate change, terrorism, antibiotic-resistant bacteria, and war. Popular culture expresses the fear associated with these global crises, obsessively portraying zombies, alien attacks, pandemics, and self-destructive technology. This book explores how end-times were envisioned in medieval Germany. The essays, written by well-established scholars, examine the period's fascination with the apocalypse by applying the most current methodological approaches to a wide range of literary genres. Drawing upon methodologies such as adaptation theory, gender analysis, space and place studies, reception studies, and memory studies, this book uncovers the rhetorical, didactic, narratological, mnemonic, thematic, cultural, and political functions of end-times in medieval German texts. Contributors: Tina Boyer, Albrecht Classen, Winfried Frey, Will Hasty, Ernst Ralf Hintz, Winder McConnell, Evelyn Meyer, Scott E. Pincikowski, Marian E. Polhill, Alexander Sager, Alexandra Sterling-Hellenbrand, Joseph M. Sullivan. Ernst Ralf Hintz is Professor of German and Medieval Studies at Truman State University. Scott E. Pincikowski is Professor of German at Hood College"--